2015
DOI: 10.1002/jmv.24291
|View full text |Cite
|
Sign up to set email alerts
|

Gallic acid induces apoptosis in human cervical epithelial cells containing human papillomavirus type 16 episomes

Abstract: The high-risk human papillomaviruses (HPV) that infect the anogenital tract are strongly associated with the development of cervical carcinoma, which is the second most common cancer in women worldwide. Therapeutic drugs specifically targeting HPV are not available. Polyphenolic compounds have gained considerable attention because of their cytotoxic effects against a variety of cancers and certain viruses. In this study, we examined the effects of several polyphenols on cellular proliferation and death of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…In this study, GA ameliorated the BPA-induced decrease in the activities of antioxidant enzymes together with the elevated levels of ROS. This is in confirmation of the antioxidant properties of GA reported earlier (Rather et al 2013;Shi et al 2016). Our findings show the ability of GA as a potent antioxidant capable of ameliorating BPA-induced oxidative stress.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, GA ameliorated the BPA-induced decrease in the activities of antioxidant enzymes together with the elevated levels of ROS. This is in confirmation of the antioxidant properties of GA reported earlier (Rather et al 2013;Shi et al 2016). Our findings show the ability of GA as a potent antioxidant capable of ameliorating BPA-induced oxidative stress.…”
Section: Discussionsupporting
confidence: 93%
“…The polyhydroxyphenolic compound, gallic acid, GA (3,4,5-trihydroxybenzoic acid), has been detected in vegetables and fruits including banana, pineapple, gallnut, grapes, apple, sumac, oak bark, lemons, and as a content of a number of beverages derived from plants including teas and fruit juices (Galati and O'Brien 2004;Madlener et al 2007). Studies have demonstrated the antiallergic, antimutagenic, anti-inflammatory, and anticarcinogenic activities of gallic acid via its antioxidant property (Rather et al 2013;Shi et al 2016). Gallic acid extracted from the rose flowers had been demonstrated to possess certain anti-oxidative properties (Li et al 2005).…”
mentioning
confidence: 99%
“…Gallic acid is widely recognized as having antioxidant and anti-tumor activities [34]. In this study, the gallic acid content gradually increased from a range of 5.02 to 5.84 ug/g DW during the germination process.…”
Section: Phenolic Acidsmentioning
confidence: 73%
“…It also down-regulated the expression of anti-apoptosis proteins such as Bcl-2 and x-linked inhibitor of apoptosis protein (Xiap). In contrast, delayed expression of pro-apoptosis related proteins was observable in non-cancerous cells and no reduction of survival-related protein expression was found in the non-cancerous cells [53].…”
Section: Effect Of P Macrocarpa On Cervical Cancermentioning
confidence: 74%